Bipolar disorder and antibodies against the N-methyl-d-aspartate receptor: A gate to the involvement of autoimmunity in the pathophysiology of bipolar illness. (August 2015) - León-Caballero, J.; Pacchiarotti, I.; Murru, A.; Valentí, M.; Colom, F.; Benach, B.; Pérez, V.; Dalmau, J.; Vieta, E.
Highlights: There is a high comorbidity between BD and autoimmune diseases. An immune dysregulation may be involved in the development of BD. NMDAR dysfunctions may have a relevant role in the pathophysiology of BD. Anti-NMDAR auto-Abs may be related with the affective symptoms in autoimmune diseases. A subgroup of BD might present increased levels of anti-NMDAR auto-Abs. Abstract: The high prevalence of comorbidity between bipolar disorder (BD) and other medical conditions, including autoimmune diseases, supports the hypothesis of the nature of BD as a biological illness category. Hence, an immune dysregulation process may play an important role in the development of at least certain subtypes of BD. Increasing evidence also suggests that the N-methyl-d -aspartate receptor (NMDAR) may be relevant in the pathophysiology of BD. A possible key mechanism underlying the physiopathology of certain autoimmune diseases that may present with affective symptoms might be the production of anti-NMDAR auto-antibodies (auto-Abs). The best characterized autoimmune anti-NMDAR disease is the anti-NMDAR encephalitis. It has been found that 4% of these patients present isolated, mostly affective, psychiatric manifestations during their illness. An interesting suggestion emerged from this overview is that the same mechanisms that trigger affective symptoms in patients with increased anti-NMDAR auto-Abs levels could be involved in the physiopathology of at least a subgroup of BD. Future studies are needed to characterize the relationship between anti-NMDAR auto-Abs and BD.